Case report: Surgical repair of congenitally corrected transposition of the great arteries with the guidance of three-dimensional printing - Zhang, Yanchun; Li, Yongnan; Ma, YuMei; Wei, Yalin; He, Fengxiao; Zhu, Yilin; Lu, Weixin; Zhao, Yinglu; Wu, Xiangyang (Frontiers in Cardiovascular Medicine, 2023)
A 10-year-old girl presented with obvious cyanosis, and the saturation of arterial blood oxygen (SpO2) was decreased to 60.5% in the outpatient examination. Computed tomography angiography (CTA) and echocardiography suggested congenitally corrected transposition of the great arteries (ccTGAs), membranous ventricular septal aneurysm (MVSA), atrial septal defect (ASD), severe pulmonary stenosis (PS), and severe tricuspid regurgitation (TR). Due to the complex pathological anatomical structures, the three-dimensional printed model was used for preoperative assessment. After a comprehensive evaluation was completed, the operation was performed by physiological correction under cardiopulmonary bypass, including the resection of MVSA, repair using the bovine pericardial patch for ASD, and linear valvuloplasty of the tricuspid valve. Due to the special anatomical structures of ccTGA, PS was treated by extracardiac pipe technique. After the operation, the patient recovered well, cyanosis disappeared, SpO2 was up to 96%, and the extracardiac pipe was well-functioning without regurgitation or obstruction.